Pembentukan Karakter Anak Usia Dini Melalui Penanaman Nilai-Nilai Kebhinekaan di Sekolah Inklusi - Meydina Hikmah Tuzzahro; Mustakimah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Inclusive schools provide a supportive environment for diversity, both in terms of social background, culture, religion, and abilities between students. Through inclusive education programs based on the values ​​of togetherness in diversity, schools play an important role in forming an attitude of tolerance, respect for differences, and a sense of unity among students. The formation of children's character is one of the important goals in every institution, especially in inclusive schools that have a diversity of students from various backgrounds. At this time, early childhood experiences a critical period, to form the foundations of a positive personality that will influence how a person behaves in the future. Instilling the values ​​of diversity emphasizes unity in diversity, becoming an important basis in the education process at the Talenta Inclusive School. This article aims to find out how the values ​​of diversity are internalized in order to form children's character from an early age. Through qualitative methods, this study collected data from observations, interviews, and school documentation. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The results of the study show that the values ​​of Bhineka Tunggal Ika, such as tolerance, cooperation, and mutual respect, are applied in teaching and learning activities, including in social interactions between students with special needs and regular students. The instillation of these values ​​has been proven to produce children's characters who are inclusive, empathetic, and respectful of differences. The conclusion of this study emphasizes the importance of instilling the values ​​of diversity from an early age in an inclusive education system to create a generation that has character, is resilient, and is ready to live in a pluralistic society.